Loss of base‐to‐apex circumferential strain gradient: A specific pattern of Fabry cardiomyopathy?. Issue 4 (2nd March 2017) - Labombarda, Fabien; Saloux, Eric; Milesi, Guillaume; Bienvenu, Boris
Abstract : Introduction and objectives: Cardiac manifestations in Fabry disease are mainly characterized by left ventricular hypertrophy (LVH). The aims of this study were (1) to describe the pattern of regional strain in patients with Fabry disease and (2) to assess whether this pattern may help differentiate patients with Fabry disease from patients with sarcomeric hypertrophic cardiomyopathy (HCM). Methods: Seventy‐seven subjects were investigated: patients with Fabry disease (n=37; 57% with LVH), patients with HCM (n=21), and healthy controls (n=19). Global and segmental longitudinal and circumferential strain (CS) analyses were performed by two‐dimensional speckle strain imaging. Base‐to‐apex longitudinal and CS gradient, defined as the peak gradient difference between averaged basal and apical strain, was calculated. Results: Longitudinal strain gradient did not differ between controls and Fabry patients without hypertrophy (respectively: −10±3.2 vs −8±4.3, P =.41) or between the HCM group and Fabry patients with hypertrophy (respectively: −7.5±4.5 vs −9±4.5, P =.37). The CS gradient was lower in Fabry patients without hypertrophy compared to the controls (respectively: 1±8 vs 14.2±9.5, P <.01), and lower in Fabry patients with hypertrophy compared to the HCM group (respectively: 0.5±8 vs 6±9, P <.01). Base‐to‐apex CS gradient was lost in both Fabry groups. Conclusion: Loss of base‐to‐apex CS gradient may be a specific left ventricular deformation pattern of Fabry cardiomyopathy in patients with and without LVH.